Charcoal-based negative carbon functional cement shaving board and preparation method thereof

By using biochar prepared by high-temperature pyrolysis to replace traditional wood shavings, combined with silicate cement, mineral blends and basalt grille fibers, biochar-based negative carbon functional cement board is prepared by cold press forming and CO2 carbonization maintenance technology, solving the problems of insufficient corrosion and mechanical properties of cement particleboard, and achieving lightweight and high-strength, thermal insulation, sound absorption and noise reduction and negative carbon emission effects.

CN119797858AActive Publication Date: 2025-04-11ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510292883.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

Existing cement particleboards are prone to corrosion during use, affecting their durability, and the soluble organic matter in wood shavings inhibits the cement hydration reaction and affects the mechanical properties.

Method used

Biochar is used to replace traditional wood shavings, biochar is prepared by high-temperature pyrolysis, and is uniformly mixed with silicate cement, mineral blends and other raw materials, basalt grating fibers are added, and biochar-based negative carbon functional cement particle board is prepared through cold pressing molding and CO2 carbonization maintenance technology.

Benefits of technology

It has achieved lightweight, high-strength, thermal insulation, sound absorption and noise reduction properties of cement particleboard, and has greatly reduced carbon emissions and realized the development of negative cement particleboard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797858A_ABST
    Figure CN119797858A_ABST
Patent Text Reader

Abstract

The invention discloses a charcoal-based negative carbon functional cement shaving board and a preparation method thereof. The preparation method comprises the following steps: pyrolyzing, crushing and screening biomass at 400-600 DEG C to obtain charcoal; the method comprises the following steps: uniformly mixing biochar, Portland cement and a mineral admixture according to a mass ratio of (40-60): (28-42): (12-18), and stirring to obtain a mixed dry material; adding water into the mixed dry material, and uniformly stirring to obtain slurry; putting part of the slurry into a mold, then adding basalt grating fibers, then adding the other part of the slurry to cover the basalt grating fibers, vibrating and paving the surface, and demolding after pressurizing to obtain a plate blank; the board blank is subjected to CO2 carbonization curing and then subjected to standard curing, and the charcoal-based negative carbon functional cement shaving board is obtained. The cement shaving board prepared through the method is light in weight, high in strength and good in durability, and meanwhile has high heat preservation and insulation performance, sound absorption and noise reduction performance and carbon negative performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid waste recycling and cement particleboard preparation, and specifically relates to a biochar-based negative carbon functional cement particleboard and a preparation method thereof. Background Art

[0002] Today, as we vigorously promote low-carbon development, green development and circular development, the importance and urgency of using biomass as a substitute or combining it with traditional building materials to form the characteristics and advantages of "sustainable biomass composite building materials" in the future development of the building materials industry are further highlighted.

[0003] Cement particleboard is one of the commonly used man-made boards. It is generally made of cement as a cementitious material and wood particles as a filling and reinforcing material. After mixing with an appropriate amount of water and additives, it is made through processes such as pressurization, molding, and curing. Compared with traditional wood boards, it has the advantages of high strength, fire resistance, moth resistance, and zero formaldehyde. It can be widely used in wall materials, indoor and outdoor decoration, and furniture manufacturing.

[0004] The invention patent with the publication number CN100387414C discloses a method for producing a lightweight cement particleboard, the process of which is as follows: select 1.0 weight part (the same below) of wood particles (absolutely dry) with a length of more than 30 mm, 0-0.5 parts of filler (absolutely dry), 0.5-3 parts of cement, 0.02-0.24 parts of additives, 1.0-2.0 parts of water, stir (spray) evenly, pave into a slab, cold press, pressure 0.2-1MPa, cold press time 20-40 hours, and naturally cure the formed board at room temperature. The lightweight cement particleboard is widely used in earthquake-proof buildings, broadcasting studios, and indoor ceiling buildings, but the particle material in the lightweight cement particleboard is easily corroded, affecting the durability.

[0005] The filler of cement particleboard is generally made of wood, but the soluble organic matter in wood will seriously inhibit the hydration reaction of cement and affect the mechanical properties of particleboard. In addition, the cellulose and lignin in wood will also slowly degrade in a long-term cement high-alkali environment, affecting the durability of particleboard. Therefore, it is necessary to develop and utilize other highly durable biomass materials to replace wood in cement particleboard.

[0006] Biochar is a porous stable material obtained by thermochemical conversion of various biomasses in an oxygen-deficient environment. The biomass comes from a wide range of sources, including forestry waste, agricultural waste, organic sludge, and livestock manure. Biochar has a tunable pore structure, rich functional groups, and active surface interface reactions. It has been widely used in soil remediation, wastewater treatment, and catalytic reactions. In recent years, studies have found that porous biochar can be used as a green additive for cement-based composites. It promotes cement hydration and improves the mechanical properties of building materials through its water retention capacity and internal curing effect.

[0007] The invention patent application with the publication number CN110238932A discloses a mildew-proof and anti-corrosion high-strength cement particleboard and a preparation method thereof. The preparation method of the invention comprises the following steps: (1) carbonizing and washing the wood particles in sequence, mixing the obtained carbonized wood particles with cement gelling agent, curing agent aqueous solution and water to obtain a mixture; (2) molding the mixture to obtain a preform; (3) curing and drying the preform in sequence to obtain the mildew-proof and anti-corrosion high-strength cement particleboard. Compared with ordinary cement particleboards that have not been carbonized and washed, the cement particleboard prepared by the invention method can effectively avoid mildew and decay of the cement particleboard, and can significantly improve the mechanical strength and durability of the cement particleboard, thereby helping to improve the service life of the cement particleboard. However, the carbonization temperature disclosed in the invention patent application is relatively low, and the wood particles are not completely converted into biochar. The carbonized wood particles only play a role in mildew and corrosion prevention, and are not very helpful for thermal insulation, noise reduction and other properties. Summary of the invention

[0008] The present invention provides a method for preparing a biochar-based negative carbon functional cement particleboard. The cement particleboard prepared by the method is light, high-strength and has good durability, and also has high thermal insulation, sound absorption and noise reduction and negative carbon properties.

[0009] The present invention provides a method for preparing a biochar-based negative carbon functional cement particleboard, comprising: The biomass is pyrolyzed at 400-600°C, crushed, and sieved to obtain biochar; The biochar, silicate cement and mineral admixture are uniformly mixed and stirred in a mass ratio of (40-60):(28-42):(12-18) to obtain a mixed dry material; Add water to the mixed dry materials and stir evenly to obtain a slurry; Putting part of the slurry into a mold and then adding basalt grid fibers, then adding another part of the slurry to cover the basalt grid fibers, vibrating and flattening the surface, and demolding after pressurization to obtain a sheet blank; The board blank is first subjected to CO2 carbonization curing and then subjected to standard curing to obtain a biochar-based negative carbon functional cement particleboard.

[0010] Preferably, the biomass is bamboo, wood and straw.

[0011] Preferably, the pyrolysis conditions are: in a CO2 atmosphere of 200±10mL / min, heating to 400-600°C at a rate of 10±1°C / min, and pyrolysis for 90-150 minutes. The appropriate pyrolysis time can provide sufficient energy to carbonize the biomass to form a porous structure.

[0012] Preferably, the size of the screened biochar is 0-5 mm, excluding the endpoint 0.

[0013] Preferably, before mixing the biochar, the biochar is first added to water and pre-soaked for 12 to 15 hours and then drained to obtain saturated surface dry conditions to improve workability when mixed with cement. Portland cement and mineral admixtures need to be placed in an oven at 105±1°C and dried to constant weight before mixing.

[0014] Preferably, the mineral admixture is industrial waste such as granulated blast furnace slag or fly ash rich in active ingredients such as calcium, silicon and aluminum, and the silicate cement is numbered PI42.5.

[0015] Preferably, the mass ratio of the added water to the mixture of silicate cement and mineral admixture is 0.38-0.42, so as to ensure that the cementitious material can fully undergo hydration reaction, bind the wood chips and provide strong mechanical properties.

[0016] Preferably, the basalt grid fiber is in a grid shape, and is added to the slurry at a mass ratio of 1% to 3% of the mixed dry material to improve the mechanical properties of the cement particleboard. The amount of basalt grid fiber added should not be too much, otherwise it will lead to a decrease in gelling properties and cracks.

[0017] Preferably, the pressure of the press molding is 4-6 MPa, and the press time is 3-5 minutes, until the sheet blank has no rebound, and then the sheet blank is demoulded.

[0018] Preferably, the parameters of the CO2 carbonization curing are: temperature 20℃±2℃, relative humidity 75%±5%, pressure 1MPa±0.1MPa, and introduction of CO2 with a purity of 99%; the working conditions in the standard curing box are: temperature 20℃±2℃, relative humidity 95%±5%, and normal pressure.

[0019] The present invention also provides a biochar-based negative carbon functional cement particleboard, and the biochar-based negative carbon functional cement particleboard is prepared by the preparation method of the biochar-based negative carbon functional cement particleboard.

[0020] Preferably, the biochar-based cement particleboard is tested according to GB / T24312-2022 "Cement Particleboard", GB / T32064-2015 "Test Method for Thermal Conductivity and Thermal Diffusivity of Building Materials by Transient Plane Heat Source" and GB / T16731-2023 "Grading of Sound Absorption Performance of Building Sound Absorption Products", and its moisture content is 8%~12%, 24h water absorption thickness expansion rate ≤2%, static bending strength is 9~12.5MPa, impact resistance test drop hammer has no through cracks, density is 900~1250kg / m 3, thermal conductivity is 0.25~0.45W / (m·K), noise reduction coefficient (NRC) ≥0.4, and the carbon footprint is negative throughout the life cycle.

[0021] Compared with the prior art, the present invention has the following beneficial effects: The present invention utilizes high-temperature pyrolysis of waste biomass to obtain biochar with low bulk density, low thermal conductivity and rich pore structure. By adding a high content of the biochar, the cement particleboard provided by the present invention has the performance of lightweight anti-corrosion, thermal insulation, sound absorption and noise reduction. At the same time, combined with CO2 carbonization curing, the carbon emission of the cement particleboard is greatly reduced, realizing the development of negative carbon cement particleboard.

[0022] The present invention controls the incorporation ratio of biochar, and simultaneously enhances the mechanical properties of the cement particle board by adding basalt grid fibers and using CO2 carbonization curing methods, so that the cement particle board provided by the present invention can not only meet the standard requirements, but also has special functionalities such as light weight, negative carbon, heat preservation and noise reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A flow chart of a biochar-based negative carbon functional cement particleboard and a preparation method provided in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0024] The present invention provides a biochar-based negative carbon functional cement particleboard and a preparation method. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0025] The biochar in the present invention is a porous stable material obtained by thermochemical conversion of various biomasses in an oxygen-deficient environment, wherein the biomass has a wide range of sources, including forestry waste, agricultural waste, organic sludge and livestock manure. Biochar has a tunable pore structure, rich functional groups and active surface interface reactions, and has been widely used in the fields of soil remediation, wastewater treatment and catalytic reactions. In recent years, studies have found that porous biochar can be used as a green additive for cement-based composite materials, promoting cement hydration and improving the mechanical properties of building materials through its water retention capacity and internal curing effect. Therefore, the use of stable and widely available biochar to replace traditional wood shavings can not only get rid of the dependence on traditional wood shavings, but also enhance the durability of cement particleboard and improve the mechanical properties of particleboard. At the same time, the low bulk density, low thermal conductivity and rich pore structure of biochar can give biochar-based cement particleboard special functionality such as light weight, heat insulation and noise reduction. The low bulk density can reduce the overall density of cement particleboard, making it lighter, reducing the burden of transportation and meeting the requirements of prefabricated buildings. The low thermal conductivity and porous structure can destroy the thermal bridging inside the particleboard, induce the dispersion of heat, and enhance the thermal insulation performance of cement particleboard. The porous structure of biochar can also produce interconnected pore structures in building materials, in which sound waves are constantly refracted and eventually dissipated into heat energy, thereby enhancing the sound insulation and noise reduction performance of cement particleboard.

[0026] The carbon footprint of biochar over its entire life cycle is -2.0~-2.6kgCO2 / kg. Using it as wood particles can significantly reduce the carbon emissions of cement particleboard. CO2 carbonization curing technology is a commonly used carbon fixation and building material curing technology. Through the mineralization reaction between high-pressure CO2 gas and the gelling components and other alkaline calcium and magnesium components in the pre-cured building materials, stable carbonate products are formed in the internal pores and interface structures of the building materials to achieve CO2 fixation. The filling effect, interface transition period elimination effect and product layer effect can significantly improve the strength and durability of building materials.

[0027] In a specific embodiment of the present invention, waste bamboo materials such as discarded disposable bamboo chopsticks, discarded bamboo tripods, and scraps from bamboo processing plants are pyrolyzed to prepare bamboo biochar, and raw materials such as biochar, silicate cement, and mineral admixtures (mineral powder, fly ash, etc.) are made into biochar-based cement particleboard through cold pressing and CO2 carbonization curing technology.

[0028] The biochar-based particleboard proposed in the specific embodiment of the present invention uses biochar prepared from waste bamboo to replace traditional wood particles, thus getting rid of the dependence on traditional wood and avoiding the problem of poor durability of traditional biomass building materials. The specific embodiment of the present invention also uses granulated blast furnace slag, fly ash and other industrial wastes to partially replace silicate cement, which not only realizes the resource utilization of waste, but also reduces the production cost and carbon emissions of cement particleboard. At the same time, the present invention utilizes the "negative carbon property" of biochar and the dual carbon fixation effect of CO2 carbonization maintenance to realize the development of negative carbon cement particleboard, and contributes to the sustainable development of the construction industry and carbon emission reduction. In addition, thanks to the excellent properties of biochar, the biochar-based cement particleboard developed by the present invention also has the properties of light weight and high strength, thermal insulation, and sound absorption and noise reduction, which can meet the increasingly diversified needs of the building materials market.

[0029] The embodiment of the present invention provides a method for preparing a biochar-based negative carbon functional cement particleboard by using biochar obtained by pyrolysis of waste bamboo to replace traditional wood shavings, using silicate cement and mineral admixtures as binders, and adding basalt grid fibers to improve mechanical properties, and using cold pressing and CO2 carbonization curing technology. Figure 1 The raw material ratios of the embodiments and comparative examples are shown in Table 1.

[0030] In order to prevent the raw materials from getting damp and clumping, which would lead to uneven mixing, it is necessary to pre-dry the silicate cement and mineral admixtures before mixing the raw materials to keep them in a uniform powder state.

[0031] Example 1: A method for preparing a biochar-based negative carbon functional cement particleboard, the specific steps are as follows: (1) Collected waste bamboo (discarded disposable bamboo chopsticks, discarded bamboo tripods, scraps from bamboo processing plants, etc.) were dried in a 105℃ oven to constant weight, and then sent to a 500℃ tube furnace for pyrolysis in a 200 mL / minCO2 atmosphere for 120 minutes to prepare bamboo charcoal. The pyrolysis furnace heating rate was 10℃ / min. When cooled to room temperature, the bamboo charcoal was taken out, crushed and sieved to obtain 0-5 mm bamboo charcoal for the preparation of particleboard; (2) Bamboo charcoal, silicate cement (PI42.5), and granulated blast furnace slag (main components include 35.7% CaO, 27.2% SiO2, 12.4% Al2O3, etc.) are uniformly mixed in a mass ratio of 40:42:18, and stirred at a speed of 300 rpm for 5 minutes to obtain a mixed dry material; the bamboo charcoal needs to be pre-soaked in water for 12 hours before mixing and then drained to obtain a saturated surface dry condition; the silicate cement and mineral admixtures need to be dried in an oven at 105°C to constant weight before mixing; (3) Weigh the required water according to the mass ratio of water: (Portland cement + granulated blast furnace slag) = 4:10, then weigh a part of the mixed dry materials, mix the water with the part of the mixed dry materials, and stir at a speed of 500 rpm for 5 minutes to obtain a fresh slurry; (4) Weigh an appropriate amount of fresh slurry and divide it into two equal parts. Pour half of the slurry into a steel mold, vibrate and flatten the surface, then add basalt grid fiber with a mass ratio of 1% of the mixed dry material, and then pour the other half of the slurry into the mold to cover the basalt grid fiber and vibrate and flatten the surface; (5) Place the steel mold in a cold press and press at a pressure of 5 MPa for 5 minutes until the board has no rebound. Then demold the board and place it in a CO2 carbonization curing box (temperature 20℃±2℃, relative humidity 75%±5%, pressure 1MPa±0.1MPa, and pass 99% pure CO2) for curing for 1 day. Then transfer it to a standard curing box (temperature 20℃±2℃, relative humidity 95%±5%, normal pressure) for curing for 6 days to obtain the finished biochar-based cement particleboard.

[0032] The performance of biochar-based cement particleboard was tested in accordance with GB / T24312-2022 "Cement Particleboard", GB / T32064-2015 "Test method for transient plane heat source of thermal conductivity and thermal diffusivity of building materials" and GB / T16731-2023 "Sound absorption performance classification of building sound absorption products". The test results are shown in Table 2.

[0033] Example 2: A method for preparing a biochar-based negative carbon functional cement particleboard, the specific steps are as follows: (1) Collected waste bamboo (discarded disposable bamboo chopsticks, discarded bamboo tripods, scraps from bamboo processing plants, etc.) were dried in a 105°C oven to constant weight, and then sent to a 500°C tube furnace for pyrolysis in a 200mL / min CO2 atmosphere for 120 minutes to prepare bamboo charcoal. The pyrolysis furnace heating rate was 10°C / min. When cooled to room temperature, the bamboo charcoal was taken out, crushed and sieved to obtain 0-5 mm bamboo charcoal for the preparation of particleboard; (2) Bamboo charcoal, silicate cement (PI42.5), and granulated blast furnace slag (main components include 35.7% CaO, 27.2% SiO2, 12.4% Al2O3, etc.) are uniformly mixed in a mass ratio of 50:35:15, and stirred at a speed of 300 rpm for 5 minutes to obtain a mixed dry material; the bamboo charcoal needs to be pre-soaked in water for 12 hours before mixing and then drained to obtain a saturated surface dry condition; the silicate cement and mineral admixtures need to be dried in an oven at 105°C to constant weight before mixing; (3) Weigh the required water according to the mass ratio of water: (Portland cement + granulated blast furnace slag) = 4:10, then weigh a part of the mixed dry materials, mix the water with the part of the mixed dry materials, and stir at a speed of 500 rpm for 5 minutes to obtain a fresh slurry; (4) Weigh an appropriate amount of fresh slurry and divide it into two equal parts. Pour half of the slurry into a steel mold, vibrate and flatten the surface, then add basalt grid fiber with a mass ratio of 1% of the mixed dry material, and then pour the other half of the slurry into the mold to cover the basalt grid fiber and vibrate and flatten the surface; (5) Place the steel mold in a cold press and press at a pressure of 5 MPa for 5 minutes until the board has no rebound. Then demold the board and place it in a CO2 carbonization curing box (temperature 20℃±2℃, relative humidity 75%±5%, pressure 1 MPa±0.1MPa, and pass 99% pure CO2) for curing for 1 day. Then transfer it to a standard curing box (temperature 20℃±2℃, relative humidity 95%±5%, normal pressure) for curing for 6 days to obtain the finished biochar-based cement particleboard.

[0034] According to GB / T24312-2022 "Cement Particleboard", GB / T32064-2015 "Test method for transient plane heat source of thermal conductivity and thermal diffusivity of building materials" and GB / T16731-2023 "Sound absorption performance classification of building sound absorption products", the basic properties, thermal conductivity and noise reduction coefficient of biochar-based cement particleboard were tested. The test results are shown in Table 2.

[0035] Example 3: A method for preparing a biochar-based negative carbon functional cement particleboard, the specific steps are as follows: (1) Collected waste bamboo (discarded disposable bamboo chopsticks, discarded bamboo tripods, scraps from bamboo processing plants, etc.) were dried in a 105°C oven to constant weight, and then sent to a 500°C tube furnace for pyrolysis in a 200mL / min CO2 atmosphere for 120 minutes to prepare bamboo charcoal. The pyrolysis furnace heating rate was 10°C / min. When cooled to room temperature, the bamboo charcoal was taken out, crushed and sieved to obtain 0-5 mm bamboo charcoal for the preparation of particleboard; (2) Bamboo charcoal, silicate cement (PI42.5), and granulated blast furnace slag (main components include 35.7% CaO, 27.2% SiO2, 12.4% Al2O3, etc.) are uniformly mixed in a mass ratio of 60:28:12, and stirred at a speed of 300 rpm for 5 minutes to obtain a mixed dry material; the bamboo charcoal needs to be pre-soaked in water for 12 hours before mixing and then drained to obtain a saturated surface dry condition; the silicate cement and mineral admixtures need to be dried in an oven at 105°C to constant weight before mixing; (3) Weigh the required water according to the mass ratio of water: (Portland cement + granulated blast furnace slag) = 4:10, then weigh a part of the mixed dry materials, mix the water with the part of the mixed dry materials, and stir at a speed of 500 rpm for 5 minutes to obtain a fresh slurry; (4) Weigh an appropriate amount of fresh slurry and divide it into two equal parts. Pour half of the slurry into a steel mold, vibrate and flatten the surface, then add basalt grid fiber with a mass ratio of 1% of the mixed dry material, and then pour the other half of the slurry into the mold to cover the basalt grid fiber and vibrate and flatten the surface; (5) Place the steel mold in a cold press and press at a pressure of 5 MPa for 5 minutes until the board has no rebound. Then demold the board and place it in a CO2 carbonization curing box (temperature 20℃±2℃, relative humidity 75%±5%, pressure 1MPa±0.1MPa, and pass 99% pure CO2) for curing for 1 day. Then transfer it to a standard curing box (temperature 20℃±2℃, relative humidity 95%±5%, normal pressure) for curing for 6 days to obtain the finished biochar-based cement particleboard.

[0036] According to GB / T24312-2022 "Cement Particleboard", GB / T32064-2015 "Test method for transient plane heat source of thermal conductivity and thermal diffusivity of building materials" and GB / T16731-2023 "Sound absorption performance classification of building sound absorption products", the basic properties, thermal conductivity and noise reduction coefficient of biochar-based cement particleboard were tested. The test results are shown in Table 2.

[0037] Comparative Example 1: A method for preparing a biochar-based negative carbon functional cement particleboard, the specific steps are as follows: (1) Collected waste bamboo materials (discarded disposable bamboo chopsticks, discarded bamboo tripods, scraps from bamboo processing plants, etc.) were dried in a 105°C oven to constant weight, and then sent to a 500°C tube furnace for pyrolysis in a 200mL / min CO2 atmosphere for 120 minutes to prepare bamboo charcoal. The pyrolysis furnace heating rate was 10°C / min. When cooled to room temperature, the bamboo charcoal was taken out, crushed and sieved to obtain 0-5mm bamboo charcoal for the preparation of particleboard; (2) Bamboo charcoal, silicate cement (PI42.5), and granulated blast furnace slag (main components include 35.7% CaO, 27.2% SiO2, 12.4% Al2O3, etc.) are uniformly mixed in a mass ratio of 30:49:21, and stirred at a speed of 300 rpm for 5 minutes to obtain a mixed dry material; the bamboo charcoal needs to be pre-soaked in water for 12 hours before mixing and then drained to obtain a saturated surface dry condition; the silicate cement and mineral admixtures need to be dried in an oven at 105°C to constant weight before mixing; (3) Weigh the required water according to the mass ratio of water: (Portland cement + granulated blast furnace slag) = 4:10, then weigh a part of the mixed dry materials, mix the water with the part of the mixed dry materials, and stir at a speed of 500 rpm for 5 minutes to obtain a fresh slurry; (4) Weigh an appropriate amount of fresh slurry and divide it into two equal parts. Pour half of the slurry into a steel mold, vibrate and flatten the surface, then add basalt grid fiber with a mass ratio of 1% of the mixed dry material, and then pour the other half of the slurry into the mold to cover the basalt grid fiber and vibrate and flatten the surface; (5) Place the steel mold in a cold press and press at a pressure of 5 MPa for 5 minutes until the board has no rebound. Then demold the board and place it in a CO2 carbonization curing box (temperature 20℃±2℃, relative humidity 75%±5%, pressure 1MPa±0.1MPa, and pass 99% pure CO2) for curing for 1 day. Then transfer it to a standard curing box (temperature 20℃±2℃, relative humidity 95%±5%, normal pressure) for curing for 6 days to obtain the finished biochar-based cement particleboard.

[0038] The performance of biochar-based cement particleboard was tested in accordance with GB / T24312-2022 "Cement Particleboard", GB / T32064-2015 "Test method for transient plane heat source of thermal conductivity and thermal diffusivity of building materials" and GB / T16731-2023 "Sound absorption performance classification of building sound absorption products". The test results are shown in Table 2.

[0039] Comparative Example 2: A method for preparing a biochar-based negative carbon functional cement particleboard, the specific steps are as follows: (1) Collected waste bamboo materials (discarded disposable bamboo chopsticks, discarded bamboo tripods, scraps from bamboo processing plants, etc.) were dried in a 105°C oven to constant weight, and then sent to a 500°C tube furnace for pyrolysis in a 200mL / min CO2 atmosphere for 120 minutes to prepare bamboo charcoal. The pyrolysis furnace heating rate was 10°C / min. When cooled to room temperature, the bamboo charcoal was taken out, crushed and sieved to obtain 0-5mm bamboo charcoal for the preparation of particleboard; (2) Bamboo charcoal, silicate cement (PI42.5), and granulated blast furnace slag (main components include 35.7% CaO, 27.2% SiO2, 12.4% Al2O3, etc.) are uniformly mixed in a mass ratio of 70:21:9, and stirred at a speed of 300 rpm for 5 minutes to obtain a mixed dry material; the bamboo charcoal needs to be pre-soaked in water for 12 hours before mixing and then drained to obtain a saturated surface dry condition; the silicate cement and mineral admixtures need to be dried in an oven at 105°C to constant weight before mixing; (3) Weigh the required water according to the mass ratio of water: (Portland cement + granulated blast furnace slag) = 4:10, then weigh a part of the mixed dry materials, mix the water with the part of the mixed dry materials, and stir at a speed of 500 rpm for 5 minutes to obtain a fresh slurry; (4) Weigh an appropriate amount of fresh slurry and divide it into two equal parts. Pour half of the slurry into a steel mold, vibrate and flatten the surface, then add basalt grid fiber with a mass ratio of 1% of the mixed dry material, and then pour the other half of the slurry into the mold to cover the basalt grid fiber and vibrate and flatten the surface; (5) Place the steel mold in a cold press and press at a pressure of 5 MPa for 5 minutes until the board has no rebound. Then demold the board and place it in a CO2 carbonization curing box (temperature 20℃±2℃, relative humidity 75%±5%, pressure 1MPa±0.1MPa, and pass 99% pure CO2) for curing for 1 day. Then transfer it to a standard curing box (temperature 20℃±2℃, relative humidity 95%±5%, normal pressure) for curing for 6 days to obtain the finished biochar-based cement particleboard.

[0040] The performance of biochar-based cement particleboard was tested in accordance with GB / T24312-2022 "Cement Particleboard", GB / T32064-2015 "Test method for transient plane heat source of thermal conductivity and thermal diffusivity of building materials" and GB / T16731-2023 "Sound absorption performance classification of building sound absorption products". The test results are shown in Table 2.

[0041] Table 1 Ratios of raw materials in specific examples and comparative examples (mass ratio)

[0042] Note 1: The water addition ratio is 0.4 of the sum of the mass of Portland cement and granulated blast furnace slag; Note 2: The incorporation ratio of basalt grid fiber is 0.01 of the sum of the mass of biochar, silicate cement and granulated blast furnace slag.

[0043] Table 2 Performance test results of specific examples and comparative examples

[0044] By comparing Example 1, Example 2, Example 3 with Comparative Example 1 and Comparative Example 2, it can be found that when the biochar addition ratio is gradually increased from 30% to 70%, the density of biochar-based cement shavings gradually decreases, the moisture content is between 6% and 16%, and the 24h water absorption thickness expansion rate is less than 2%, which meets the requirements of the standard GB / T24312-2022 "Cement Particleboard". At the same time, its thermal conductivity gradually decreases, the noise reduction coefficient (NRC) gradually increases, and the thermal insulation and sound insulation performance is improved. In addition, since biochar is a good negative carbon material, as the biochar addition ratio increases, the carbon emissions of biochar-based cement particleboard gradually decrease and reach a negative value, which can contribute to the carbon emission reduction cause of the construction industry. However, as the proportion of biochar addition increases, the static bending strength of biochar-based cement particleboard gradually decreases. The static bending strength of cement particleboard specified in the standard GB / T24312-2022 "Cement Particleboard" needs to be ≥9MPa. In Comparative Example 2, when the biochar incorporation ratio is 70%, the surface strength is less than 9MPa, which does not meet the standard requirements of "Cement Particleboard". At the same time, slight through cracks appear on the surface during the impact test. Therefore, the incorporation ratio of biochar in biochar-based cement particleboard should not be too high (more than 60%), otherwise the mechanical properties of the product will not meet the standard requirements. At the same time, the incorporation ratio of biochar should not be too low. For example, in Comparative Example 1, the product density is too high, the thermal insulation and noise reduction performance is poor, the cost and carbon emissions are increased, and it cannot meet the market demand in actual application.

[0045] In general, the increase in the biochar incorporation ratio will lead to a decrease in the mechanical properties of the biochar-based cement particleboard, but the prepared product is lighter and carbon-negative, and the thermal insulation and sound absorption and noise reduction performance are enhanced. However, too high a biochar incorporation ratio will cause the mechanical properties of the biochar-based cement particleboard to not meet the standard requirements, so the biochar incorporation ratio should be reasonably selected according to the needs of the actual application. The preferred biochar incorporation ratio recommended by the present invention is 60%.

[0046] The above is only a preferred embodiment of the present invention. Although the present invention has disclosed the preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a biochar-based negative carbon functional cement particleboard, characterized in that: include: The biomass is pyrolyzed at 400-600°C, crushed, and sieved to obtain biochar; The biochar, silicate cement and mineral admixture are uniformly mixed and stirred in a mass ratio of (40-60):(28-42):(12-18) to obtain a mixed dry material; Add water to the mixed dry materials and stir evenly to obtain a slurry; Putting part of the slurry into a mold and then adding basalt grid fibers, then adding another part of the slurry to cover the basalt grid fibers, vibrating and flattening the surface, and demolding after pressurization to obtain a sheet blank; The board blank is first subjected to CO2 carbonization curing and then subjected to standard curing to obtain a biochar-based negative carbon functional cement particleboard.

2. The method for preparing the biochar-based negative carbon functional cement particleboard according to claim 1, characterized in that: The biomass is bamboo, wood and straw.

3. The method for preparing the biochar-based negative carbon functional cement particleboard according to claim 1, characterized in that: The pyrolysis conditions are as follows: in a CO2 atmosphere of 200±10 mL / min, heating to 400-600°C at a rate of 10±1°C / min, and pyrolysis for 90-150 minutes.

4. The method for preparing the biochar-based negative carbon functional cement particleboard according to claim 1, characterized in that: The size of the sieved biochar is 0~5mm, excluding the endpoint 0.

5. The method for preparing the biochar-based negative carbon functional cement particleboard according to claim 1, characterized in that: Before mixing the biochar, the biochar was first added to water and pre-soaked for 12 to 15 hours and then drained. The silicate cement and mineral admixtures were placed in an oven at 105±1° C. and dried to constant weight before mixing.

6. The method for preparing the biochar-based negative carbon functional cement particleboard according to claim 1, characterized in that: The mineral admixture is industrial waste such as granulated blast furnace slag or fly ash, which is rich in active components such as calcium, silicon and aluminum.

7. The method for preparing the biochar-based negative carbon functional cement particleboard according to claim 1, characterized in that: The mass ratio of added water to the mixture of silicate cement and mineral admixtures is 0.38~0.

42.

8. The method for preparing the biochar-based negative carbon functional cement particleboard according to claim 1, characterized in that: The basalt grid fiber is in a grid shape and is added to the slurry at a mass ratio of 1% to 3% of the mixed dry material.

9. A biochar-based negative carbon functional cement particleboard, characterized in that: The biochar-based negative carbon functional cement particleboard is prepared by the preparation method of the biochar-based negative carbon functional cement particleboard.

10. The biochar-based negative carbon functional cement particleboard according to claim 9, characterized in that: The biochar-based negative carbon functional cement particleboard has a moisture content of 8% to 12%, a 24h water absorption thickness expansion rate of ≤2%, a static bending strength of 9 to 12.5 MPa, and no through cracks in the impact resistance test of a falling hammer, and a density of 900 to 1250 kg / m 3 , thermal conductivity is 0.25~0.45W / (m·K), noise reduction coefficient (NRC) ≥0.4, and the carbon footprint is negative throughout the life cycle.

Citation Information

Patent Citations

  • Method for preparing liquid state silicon series charing antisepsis wood bamboo

    CN101234497A

  • Lightweight basalt fiber reinforced ceramsite concrete board

    CN104234303A

  • Recycled aggregate pervious concrete as well as preparation method and application thereof

    CN118221398A

  • Carbonization-cured high-toughness fiber cement board as well as preparation method and application thereof

    CN118221403A

  • Charred bamboo board

    JP1995150645A